Economia da saúde no Brasil: Trajetória e contribuiç\~oes do Ipea para sua institucionalizaç\~ao no setor público - Sérgio F. Piola; Fabiola Sulpino Vieira; Liliane Cristina Gonçalves Bernardes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
Health economics (HE) is a relatively new field of knowledge, whose structuring began in the early 1960s, although studies on the intersection between economics and health date back to earlier periods. Considering the contributions of this field to the improvement of the Brazilian health system and the context of celebrating the 60th anniversary of the Institute for Applied Economic Research (Ipea), this Discussion Paper was prepared to highlight the institute's contribution to the development of HE in the Brazil's public sector. To this end, documentary and bibliographic research have carried out in the collections of the institution and other organizations that actively participated in this process in the country. The text addresses different concepts of HE, traces the evolution of the debate between economics and health, both globally and in Brazil, and explores the thematic field of HE. From a historical perspective, it analyses the process of institutionalization of HE in Brazil and discusses the differences between health political economy and health economics. In addition, it presents an overview of current research groups, sources of information, and the application of HE knowledge in the Unified Health System (SUS). The text dedicates a section to discussing Ipea's contributions to the development of HE in the Brazilian public sector. In this regard, it highlights the institution's pioneering work back in the 1980s, its participation in the creation of the Brazilian Association of Health Economics (ABrES), the publication of a book on HE, the development of the Health Economics Project in partnership with the Brazilian Ministry of Health and the Department for International Development (DFID) of the United Kingdom. Additionally, its collaboration in the development and preparation of Brazilian health accounts and its technical production in the field of health economics. Finally, it highlights some perspectives on Ipea's ongoing work in this field.
Keywords: A12; I10; 330; health care economics and organizations; health systems; Unified Health System; Institute for Applied Economic Research; Brazil